Investigation of the role of pH on structural and morphological properties of titanium dioxide nanoparticles. Issue 1 (May 2020) - Sadiq, S A; Waseem, Z; Hanif, S; Riaz, S; Hayat, K; Batool, A I F; Jamil, Y; Naz, M Y; Anwar, H
Abstract: In the present research work, titanium dioxide (TiO2 ) nanoparticles were synthesized by sol-gel method in which titanium tetraisopropoxide (TTIP) used as a precursor and the effect of pH on their structural and morphological properties was investigated systematically. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the prepared samples. The acidity-alkalinity of the gel was adjusted to different pH values (1, 4, 7 and 10) by using respective media, i.e. HCl and NH4 OH. The results showed that from strong acidic media to strong basic media, the average particle size was found to increase from 14 nm at pH 1 to 20 nm at pH 10, whereas the average particle size was 19 nm at pH 7. All peaks in XRD patterns perfectly indexed to the stable anatase tetragonal phase except sample at pH 1, where some traces of rutile phase was also present. XRD results showed the formation of single phase high purity nanoparticles. TiO2 nanoparticles showed homogeneous morphology with low agglomeration at pH 7 and pH 10.